ETIOPATHOGENESIS AND CLINICAL MANIFESTATIONS OF ACROMEGALY: PATHOPHYSIOLOGICAL MECHANISMS AND SYSTEMIC COMPLICATIONS (International journal of medical sciences, 2026)
Acromegaly is a rare, chronic endocrine disorder characterized by prolonged exposure to excessive growth hormone (GH) and insulin-like growth factor-1 (IGF-1), most commonly resulting from a GH-secreting pituitary adenoma. Despite its insidious onset, acromegaly is associated with substantial morbidity and increased mortality, primarily due to cardiovascular, metabolic, respiratory, and neoplastic complications. A delayed diagnosis remains a major clinical challenge, as early manifestations are often subtle and progress slowly over years.The etiopathogenesis of acromegaly involves dysregulation of the hypothalamic–pituitary–somatic axis, leading to autonomous GH secretion and subsequent elevation of circulating IGF-1. At the molecular level, somatic mutations, particularly in the GNAS gene, play a crucial role in pituitary adenoma development and hormonal hypersecretion. Persistent activation of GH and IGF-1 signaling pathways induces widespread anabolic, mitogenic, and anti-apoptotic effects, resulting in tissue overgrowth, organomegaly, and structural remodeling of multiple organ systems.Clinically, acromegaly presents with a broad spectrum of manifestations affecting the musculoskeletal, cardiovascular, respiratory, metabolic, and neurological systems. Characteristic phenotypic features include acral enlargement, facial dysmorphism, and soft tissue hypertrophy, while systemic complications such as cardiomyopathy, arterial hypertension, insulin resistance, type 2 diabetes mellitus, obstructive sleep apnea, and increased risk of malignancies significantly contribute to disease burden. The heterogeneity of clinical presentation underscores the importance of a multidisciplinary approach to diagnosis and management.This review provides a comprehensive overview of the etiopathogenetic mechanisms underlying acromegaly and highlights the systemic nature of its clinical manifestations. A deeper understanding of the pathophysiological processes involved is essential for early recognition, risk stratification, and optimization of therapeutic strategies aimed at reducing long-term complications and improving patient outcomes.